2023
DOI: 10.48550/arxiv.2301.02719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SDSS DR17: The Cosmic Slime Value Added Catalog

Abstract: The "cosmic web", the filamentary large-scale structure in a cold dark matter Universe, is readily apparent via galaxy tracers in spectroscopic surveys. However, the underlying dark matter structure is as of yet unobservable and mapping the diffuse gas permeating it lies beyond practical observational capabilities. A recently developed technique, inspired by the growth and movement of Physarum polycephalum 'slime mold', has been used to map the cosmic web of a low redshift sub-sample of the SDSS spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…As a starting point for the hyperparameter values, we use previous knowledge of running the MCPM algorithm as well as a priori knowledge based on physical considerations. From the BP simulation, the optimal sampling sharpness was found to be 2.5 at z = 0 and 2.2 at z = 0.5 (Wilde et al 2023). Since the cosmic web becomes more condensed over time, i.e., matter collapses into denser filamentary networks owing to the gravitational pull of structures of ever-increasing masses, we decrease the sampling sharpness with increasing redshift.…”
Section: Calibrating Input Parametersmentioning
confidence: 88%
See 2 more Smart Citations
“…As a starting point for the hyperparameter values, we use previous knowledge of running the MCPM algorithm as well as a priori knowledge based on physical considerations. From the BP simulation, the optimal sampling sharpness was found to be 2.5 at z = 0 and 2.2 at z = 0.5 (Wilde et al 2023). Since the cosmic web becomes more condensed over time, i.e., matter collapses into denser filamentary networks owing to the gravitational pull of structures of ever-increasing masses, we decrease the sampling sharpness with increasing redshift.…”
Section: Calibrating Input Parametersmentioning
confidence: 88%
“…Since the cosmic web becomes more condensed over time, i.e., matter collapses into denser filamentary networks owing to the gravitational pull of structures of ever-increasing masses, we decrease the sampling sharpness with increasing redshift. The persistence coefficient parameter is somewhat dependent on the sparseness of the input data, but previous applications of MCPM (e.g., Burchett et al 2020;Elek et al 2022;Wilde et al 2023) have found it to be optimally around 0.9. The sense distance parameter should roughly follow the volume of the data cube and resolution of the trace field.…”
Section: Calibrating Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…) . These are more realistic minimum masses compared to those of large observational surveys such as Sloan Digital Sky Survey (SDSS; e.g., Strauss et al 2002) DR17 (see, e.g., Wilde et al 2023 and our Section 4.3). However, the sharp drop in the number of galaxies in TNG with these higher masses yields increasingly fewer input tracers for DISPERSE, which result in far fewer identified filaments and nodes than in our fiducial…”
Section: Reconstructing the Cosmic Web With Dispersementioning
confidence: 91%
“…We are currently applying a new state-of-theart cosmic web reconstruction algorithm called the Monte Carlo Physarum Machine (MCPM), inspired by the Physarum polycephalum (slime mold) organism (Elek et al 2021(Elek et al , 2022, to compare to the local density estimation and global cosmic web characterization from DISPERSE. This method produces continuous cosmic matter densities (as opposed to discrete DTFE densities at the locations of galaxies) and has been applied successfully to both theoretical and observational data sets (e.g., Burchett et al 2020;Simha et al 2020;Wilde et al 2023).…”
Section: Other Caveatsmentioning
confidence: 99%